Plasma Spraying of Kaolinite for Preparing Reactive Alumino‐Silicate Glass Coatings. Issue 47 (15th December 2022) - Warr, Laurence N.; Wolff, Thorben; Testrich, Holger; Grathoff, Georg; Kruth, Angela; Foest, Rüdiger
Abstract: Thermally treated kaolinite is used to develop a range of alumino‐silicate‐based precursor materials but its behavior during plasma spraying has not been well‐researched. In this study, two types of kaolinite samples were investigated in the form of low defect (KGa‐1b) and high defect (KGa‐2) varieties. The extreme temperatures of the plasma stream (up to 20 000 K) induced flash melting to produce a highly porous alumino‐silicate glass without any crystallization of new Al−Si oxide minerals. The glass is comprised largely of intact or deformed spheres (average diameters 1.14–1.44 μ m), which indicates rapid quenching and solidification before impact. The subspherical structures contain up to 40 % closed pore space caused by the rapid escape of water during melting. The low‐density, porous alumino‐silicate glass coatings with predicted specific surface areas (>0.95 m 2 /g) and hardnesses >1.8 GPa represent a potentially reactive but physically stable substrate ideal for further chemical functionalization. Abstract : We thermally treated kaolinite samples using the extreme temperatures of a plasma stream (up to 20 000 K) to produce a highly porous alumino‐silicate glass without any crystallization of new Al−Si oxide minerals. The subspherical melt structures (average diameters in the range of 1.14–1.44 μ m) contain up to 40 % closed pore space and represent a potentially reactive but physically stable substrate suitable for further chemical functionalization.